Multifactor Evaluation of Multiple Service Support and Optimization of Working Resistance of New Support Based on Dynamic Pressure. (4th August 2020) - He, Fulian; Li, Liang; He, Wenrui; Li, Xiaobin; Lv, Kai; Qin, Binbin; Xu, Xuhui
Abstract : The scientific and feasible method is extremely important for the evaluation of whether the support of coal mines needs to be scrapped, but it has not been formed. If the support cannot be continued to use, the determined reasonable working resistance of the support before the primary mining of coal seam should be optimized. Based on the field measurement and theoretical analysis, the concept of the actual rated working resistance of the support is proposed and analyzed accurately; the total amount of roof subsidence of circulating multiple coal cutting cycles during periodic pressure is calculated; the support performance is evaluated by multifactors; a new method for determining the reasonable working resistance of the support based on dynamic pressure is proposed. The study found that the safety valve of support is opened in advance and the resistance loss rate is large; the total amount of roof subsidence during periodic pressure is high; FAHP + EWM evaluation score of support system performance is 63.31 points. The scientific evaluation of multifactors showed that the support has reached service life, and as a result, the new 105 working faces required replacement with new support. The reasonable working resistance of the support in the 3-1 coal seam is optimized according to the new method based on dynamic pressure. This study can greatly improve the safety of roof control in the working face.